A critical analysis of factors influencing internet diffusion in South Africa and its implications on the rollout of e-government services - Senatore, Luca (My University, 2010)
Abstract Staying up-to-date with Internet and other Information and Communication Technology developments is vital for a country’s economic growth and for a country to stay internationally competitive. Despite the rapid growth and uptake of the Internet around the world, South Africa has continued to struggle to keep up with this trend as the number of people who have access to the Internet is relatively low. Numerous factors continue to have a large effect on the diffusion of the Internet which in turn leads to implications for the uptake and rollout of e-Government services. Regulatory issues, ineffective policies, increasing State involvement, obsolete Universal Service Obligations, and a weak, underfunded regulator continue to hinder the widespread uptake of Internet and high speed Internet offerings. The low diffusion of Internet has lead to the South African government investing a large amount of capital into e-Government projects and strategies which are only benefiting a small portion of the population and thus exacerbating the ever growing digital divide.